Sloglish or the Mixing/Switching of Slovene and English in Slovene Blogs - Šabec, Nada (Slavia Centralis, 2020)
The article discusses the impact of the Internet on language use and, more specifically, analyzes the frequent mixing/switching of Slovene and English in Slovene blogs (so-called Sloglish). This new discourse type, combining elements of written and oral communication, is highly interactive in nature and allows for flexibility, variation and language innovation. On the other hand, some see it as too globalized and uniform as well as a threat to the language norm. Slovene blogs are analyzed linguistically (vocabulary, syntax, spelling, punctuation) and interpreted from the sociolinguistic and pragmatic perspectives (the issue of personal, cultural and social identities of bloggers; local vs. global).
Keywords: blogs; sloglish; code switching; Slovene; English; identity